Side effects of fluoroquinolone antibiotics: dysglycemia and psychical disorders - A. V. Kuzmina; A. R. Titova; T. S. Polikarpova; I. L. Asetskaya; V. A. Polivanov (Лечащий Врач)
The article deals with the results of foreign studies and data from the Russian pharmacovigilance database of spontaneous reports that characterize side effects of all fluoroquinolone antibiotics for systemic use — dysglycemia and psychical disorders.